Monitoring VHA Optometric Eye Exam Services, Nation-Wide, 2014–2016. Issue 9 (13th March 2018) - Fant, Gregory; Backus, Lisa
Abstract: Introduction: It is important to monitor the use of optometric services by Veterans and consider the implications for other optometric and vision rehabilitation services. We did not find public health reports documenting the recent utilization of Veterans Health Administration (VHA) optometric eye exam services. Methods: A cross-sectional study design was used in this secondary data analysis report. We were interested in reporting on the number of Veterans using the VHA system with at least one VHA optometric eye exam service in 2014, 2015, or 2016 within a VHA optometry clinic. The data from Veterans were derived from the VHA Corporate Data Warehouse. Results: The number of unique Veteran patients who had at least one indication of VHA optometric eye exam service, nation-wide, increased from 1.4 million Veteran patients in 2014 to 1.6 million patients in 2016. The percentage of Veterans using VHA optometric eye exam services out of all unique VHA patients receiving care in the VHA system in 2014, 2015, and 2016 was 25.4%, 25.8%, and 26.8%, respectively. During each year of this time period, about 94% of the Veteran patients were male using optometric eye exam services. Florida, California, Texas, Ohio, and New York had the largest number of Veterans using optometric eye exam services, at least once, in 2014, 2015, or 2016. Conclusion: Veteran patients who made at least one VHA optometric eye exam service visit, nation-wide, increased from 2014 to 2016. Data showed that Veteran patients in the older age groups (age 55 and greater) used optometric eye exam services differently when compared with Veterans in the younger age groups. This difference may invite consideration of the differing optometric needs of these two, broad groups of eligible Veterans in order to expand access to VHA optometric clinical services.